Heroes' feast : the official Dungeons & Dragons cookbook - Newman, Kyle, 1976-; Peterson, Jon; Witwer, Michael; Ried, Adam (Ten Speed Press, 2020)
"From the D&D experts behind Dungeons & Dragons Art & Arcana comes a cookbook that invites fantasy lovers to learn about their favorite fictional cultures through their unique cuisines and lifestyles. 80 recipes inspired by the magical world of Dungeons & Dragons--perfect for a solo quest or a feast shared with fellow adventurers"--